Reconstrução paleohidrologica do Lago Santa Ninha, Várzea de Curuai, Pará, Brasil - Moreira, Luciane Silva (2008)
Amazonian Rivers are accompanied, during their course, by floodplains, which are named várzeas . It is known that these regions have a great potential in the storage of organic matter, which in turn, provides important information about climate change occurred in the past. Knowledge of these changes allows the understanding of how ecosystem may respond to future changes in climate. The physical, chemical and geochemical characteristics of lacustrine sediments were studied to reconstructed paleohydrological control on sedimentation in an Amazonian floodplain. Two cores were collected at the Lago Grande de Curuai floodplain, in Santa Ninha lake, located on the right margin of the Amazon River at 850km of the estuary. Water content, granulometry, radiocarbon datation, microscopic analyses, organic carbon and nitrogen content and δ13C were used to characterize the sedimentary processes. The core TA12 is 210 cm-long and the TA14 has 270cm that correspond to 5700 years cal BP. The core points out different sedimentary environments: a flooded vegetation at the base of the core till 5000 cal yrs BP is substituted by graminea banks changing to a floodplain encompassing prolonged annual dryness at 4000 cal yrs BP. Since 700 BP the present day varzea lake, permanently overflooded, has been installed. These changes are interpreted as a response to an increase in the level of water in the river during the floods, which in turn are consequences of climate change occurring in the region.